Relasi Sosial Anak Berkebutuhan Khusus Pada Keluarga Single Parent Di Desa Kadubereum Kabupaten Serang - Muminah, Siti (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research began with the author's interest when he saw single parents, mothers who had multiple roles in the family to support, care for and educate their children alone. However, caring for children with special needs is not easy because of difficulties in interacting and difficulty understanding what they want. This focuses on the role of single parents towards children with special needs in interacting with the surrounding environment and being able to care for their children who have limitations without help from other family members in a tenacious and sincere manner. In contrast to parents who care for normal children, parents with children with special needs certainly experience a lot of pressure and problems that parents in general do not experience. The aim of this research is to examine the social relations of children with special needs in single parent families in Kadubereum village, Serang district. The method used to answer the problems in this research is a qualitative approach. In-depth interviews are data collection techniques that are based on intensive conversations with a purpose. In-depth interviews are a primary data collection procedure that is carried out by conducting thorough face-to-face interviews using an interview guide. The theory used is functional structural theory. The informants in this research were four single parents who had children with special needs. The subject determination technique used was purposive. The data collection technique used was in-depth interviews. Based on the research results found by researchers, namely: (1) The social relations of children with special needs in single parent families in Kadubereum village are not going well because there are obstacles for each child in communicating. (2) children with special needs are children who have limitations both physically and emotionally which significantly influence their growth and development process. This is the reason they need extra help and support to reach their potential. (3) single parents have multiple roles in the family to provide for, care for, and educate children alone, but caring for children with special needs is not easy because of the difficulties in interacting and the difficulty in understanding what is wanted.